Rehabilitation of Executive Functions in Patients with Chronic Acquired Brain Injury with Goal Management Training, External Cuing, and Emotional Regulation: A Randomized Controlled Trial. (26th January 2016) - Tornås, Sveinung; Løvstad, Marianne; Solbakk, Anne-Kristin; Evans, Jonathan; Endestad, Tor; Hol, Per Kristian; Schanke, Anne-Kristine; Stubberud, Jan
Abstract: Executive dysfunction is a common consequence of acquired brain injury (ABI), causing significant disability in daily life. This randomized controlled trial investigated the efficacy of Goal Management Training TM (GMT) in improving executive functioning in patients with chronic ABI. Seventy patients with a verified ABI and executive dysfunction were randomly allocated to GMT ( n =33) or a psycho-educative active control condition, Brain Health Workshop (BHW) ( n =37). In addition, all participants received external cueing by text messages. Neuropsychological tests and self-reported questionnaires of executive functioning were administered pre-intervention, immediately after intervention, and at 6 months follow-up. Assessors were blinded to group allocation. Questionnaire measures indicated significant improvement of everyday executive functioning in the GMT group, with effects lasting at least 6 months post-treatment. Both groups improved on the majority of the applied neuropsychological tests. However, improved performance on tests demanding executive attention was most prominent in the GMT group. The results indicate that GMT combined with external cueing is an effective metacognitive strategy training method, ameliorating executive dysfunction in daily life for patients with chronic ABI. The strongest effects were seen on self-report measures of executive functions 6 months post-treatment, suggesting that strategies learned in GMT were applied and consolidated in everyday life after the end of training. Furthermore, these findings show that executive dysfunction can be improved years after the ABI. ( JINS, 2016, 22, 436–452)